X-ray line reabsorption in a rapidly expanding plasma - Patel, P; Wolfrum, E; Renner, O; Loveridge, A; Allott, R; Neely, D; Rose, S; Wark, J (2000)
We present high-resolution spectroscopic measurements of the optically thick hydrogen-like Al Ly-α line shape from a cylindrically expanding plasma. The cylindrical expansion is produced by symmetrically irradiating a 120 μm diameter coated wire target with six beams of the VULCAN Nd:glass laser at an irradiance of 2×1014Wcm-2. Small shifts in the line position and changes in the line shape can be attributed to radiation emitted from different regions of the plasma and passing through different gradients in plasma density, temperature, and velocity. The experimental profiles are compared to a time-dependent hydrodynamics code incorporating a Sobolev escape probability treatment of the radiative transport. © 2000 Elsevier Science B.V.